ANGIOTENSIN-(1-7)/MAS AXIS AND VASCULAR INFLAMMATION - Yang, Guang; Meng, Fanxing; Wang, Jialin; Zhao, Yanping; Zhao, Linlin (European Scientific Journal, ESJ, 2015)
Atherosclerosis, as a potentially serious condition, has become one of the most prevalent causes of mortality over the world. RAS (Reninangiotensin- system) is recognized to be a key role in the development of atherosclerosis, which considered as a chronic inflammatory disease. Ang II (angiotensin II) is proven to cause atherosclerosis, hypertension and aortic aneurysms. While activation of Mas receptors by Ang-(1-7) [angiotensin-(1- 7)] shows an important role in prevention of atherosclerosis. The activation of Ang-(1-7)/Mas receptor axis counteracts Ang II-induced hypertension, inflammation, fibrosis and apoptosis responses. We have concluded that, the relationship between Ang-(1-7)/Mas axis and vascular inflammation could be the paving-stone of the avoidance and novel treatment for atherosclerosis. The scope of this study is to review the relationship between Ang-(1-7)/Mas axis and vascular inflammation in the development of atherosclerosis.